SOSIALISASI PELATIHAN MICROSOFT EXCEL BERBASIS VISUAL (DASHBOARD) UNTUK MENINGKATAN KOMPETENSI SISWA SMK NURUL HUDA BAROS - Arianto, Ichwan Putra; Jasmine, Veronika; Riska, Riska; Salsabila, Maulani Adinda; Alfiansyah, Pramudya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community service is one of the contributions of universities in supporting human resource development, particularly in enhancing students' competencies. One of the barriers faced by students is their lack of visual skills in operating Microsoft Excel. This community service activity carries the theme